High temperature induced metabolic reprogramming and lipid remodeling in a high-altitude fish species, Triplophysa bleekeri - Yuan, Dengyue; Wang, Haoyu; Liu, Xiaoqin; Wang, Siya; Shi, Jinfeng; Cheng, Xinkai; Gu, Haoran; Xiao, Shijun; Wang, Zhijian (Frontiers in Marine Science, 2022)
The effect of thermal changes on the physiology and behavior of fish is a major research focus in the face of ongoing global warming. There is little information about the effects of temperature increase on fish in the wild. However, the consequences of temperature increase on fish in controlled laboratory conditions can provide insights into what can be expected in the wild. Triplophysa bleekeri, a high-plateau fish, exhibits high sensitivity to high temperatures, suggesting it to be a good model to investigate the impact of temperature increase on fish. In this study, we analyzed the effect of gradual temperature increase on transcriptional and metabolic levels of T. bleekeri subjected to a gradual temperature change of 0.5°C/day until temperatures of 10°C, 13°C, 16°C, and 19°C were reached. Transcriptomics results of the liver, gut, spleen, and trunk kidney showed that metabolic pathways are widely involved in the response to increased temperatures in T. bleekeri. Lipidomics results further indicated that the lipid composition was altered by increased temperatures, and three lipids (PC 14:0e/22:1, PC 18:0e/22:5, and TAG 14:3-21:2-21:2) were identified as potential biomarkers of heat stress in T. bleekeri. Moreover, a decline in unsaturated fatty acid levels was observed in T. bleekeri under high temperatures. These results suggest that high temperatures modify the metabolomic pathways. Overall, our results help improve the understanding of physiological responses in fish to increased temperatures, and provide valuable information predicting the consequences of global warming on fish.